Pemaknaan Ni’mal Abdu Dalam Quran : Studi Tafsir Al Munir Wahbah Az-Zuhaili: THE MEANING OF NI'MAL ABDU IN THE QURAN: A STUDY OF TAFSIR AL MUNIR WAHBAH AZ-ZUHAILI - Adirasa, Ery Santika; Zadittaqwa, Mohammad; Fitriani, Laily (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2024)
One interesting word that catches attention is